2020
DOI: 10.1159/000506075
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of PD-1, PD-L1 and CD8 Gene Expression Levels in Gastric Cancer

Abstract: Introduction: Anti-programmed cell death 1 (PD-1) therapies have shown promising clinical activity against gastric cancer (GC). We evaluated the clinical significance of immune-related gene expression in GC tissues to better understand the tumor immune microenvironment. Methods: PD-1, PD-1 ligand 1 (PD-L1) and CD8 mRNA levels and clinicopathological factors, including survival, were examined by quantitative RT-PCR in 155 GC patients who underwent surgery. PD-1 and PD-L1 expression in tumor tissue from 24 GC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(44 reference statements)
2
10
0
1
Order By: Relevance
“…In particularly, patients with higher PRIs have higher expression levels of ICI genes (TIM-3, PD-L1 and CTLA-4). However, it is still controversial that PD-L1 expression is a favorable or adverse prognostic factor in GC according to previous researches (72)(73)(74)(75)(76)(77). As illustrated before, TGF-b, IL-6, IL-10 and TIM3 could directly or indirectly promote EMT or peritoneal metastasis which was in line with our findings (78, 79), and it is reasonable to speculate that antibodies targeting these molecules may be a preferable choice for PR high risk subgroup.…”
Section: Discussionsupporting
confidence: 89%
“…In particularly, patients with higher PRIs have higher expression levels of ICI genes (TIM-3, PD-L1 and CTLA-4). However, it is still controversial that PD-L1 expression is a favorable or adverse prognostic factor in GC according to previous researches (72)(73)(74)(75)(76)(77). As illustrated before, TGF-b, IL-6, IL-10 and TIM3 could directly or indirectly promote EMT or peritoneal metastasis which was in line with our findings (78, 79), and it is reasonable to speculate that antibodies targeting these molecules may be a preferable choice for PR high risk subgroup.…”
Section: Discussionsupporting
confidence: 89%
“…A meta-analysis showed that PDL1 negativity was associated with better overall survival in GC 24 . Low PD1, PDL1, and CD8 mRNA levels were more significantly associated with a poor prognosis 40 . A study revealed that CD68+ TAMs had no significant effect on OS 41 .…”
Section: Discussionmentioning
confidence: 92%
“…PDL1 overexpression has been associated to higher number of lymph node metastasis, larger tumor size, increased depth of invasion and poorer overall survival in various cancers [ 58 , 61 ]. According to a previous study, PD1, PDL1 and CD8 mRNA levels were significantly higher in undifferentiated GC [ 22 ]. More recently, it was demonstrated that PDL1 overexpression was a worse prognostic factor in GC [ 19 ].…”
Section: Discussionmentioning
confidence: 97%
“…PDL1 expression has been reported in a wide variety of solid tumors, including lung cancer, hepatocellular carcinoma and intra-hepatic cholangiocarcinoma, gastric, colorectal, pancreatic, ovarian, breast, cervical and oral cancer, head and neck squamous cell carcinomas, nasopharyngeal, esophageal, urothelial and renal cell cancer, nephroblastoma, melanoma and gliomas [ 58 , 59 ]. It has been suggested that CD8 + T cells upregulate PD1 expression and secrete IFN-γ when they encounter tumor antigens, resulting in the upregulation of PDL1 expression on tumor cells and immune cells and the ligation of PDL1 with PD1 will decrease T cell function and create a negative feedback mechanism that decreases antitumor immunity leading to tumorigenesis [ 22 ]. In contradiction with our observation, no statistically significant differences were found with regard to PDL1 mRNA levels within normal and GC specimens as previously verified by Chen et al [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation